Numerical investigation of the free vibration of partially Clamped rectangular plates - Gharaibeh, Mohammad A.; Obeidat, Amr M.; Obaidat, Mazin (Zielona Góra: Uniwersytet Zielonogórski)
This paper studies the free vibration characteristics of rectangular plates with partially clamped edges around the corners using the finite element method. ANSYS Parametric Design Language (APDL) was utilized to produce the finite element (FE) models and to run the analysis. The FE models were used to obtain the plate first natural frequency and mode shape.
Keywords: elastic plates; plates with partially clamped edges; natural frequencies and mode shapes; finiteelement analysis